The Tradition of Mengambat Boru in the Walimatul ‘Urs Procession: A Da'wah Study of Marriage Traditions - Muhammad Amson Nasution; Nashrillah Nashrillah (Madania: Jurnal Ilmu-Ilmu Keislaman, 2026)
This study examines the Mengambat Boru tradition within the Walimatul ‘Urs procession in Tanjung Baringin Village from a cultural da’wah perspective. The research aims to explore how the tradition is practiced and interpreted, to identify the da’wah values embedded within it, and to analyze its relevance in the context of contemporary socio-cultural dynamics. This study employs a qualitative approach with a phenomenological orientation, focusing on understanding the lived experiences of community members. Data were collected through in-depth interviews, participant observation, and document analysis, and were analyzed using an interpretative phenomenological approach. The findings reveal that the Mengambat Boru tradition embodies three interconnected dimensions: emotional-familial, social-collective, and religious-spiritual values. These dimensions demonstrate that the tradition functions not only as a cultural ritual but also as a medium of cultural da’wah, where Islamic teachings are conveyed through symbolic actions, advice, and communal participation. Furthermore, the study identifies a growing tension between cultural preservation and socio-economic pressures, which may influence the transformation of the tradition’s meaning and practice. This study contributes to the discourse on cultural da’wah by highlighting the role of local traditions as dynamic spaces for the internalization and expression of Islamic values. It also offers practical insights for maintaining a balance between preserving cultural identity and ensuring alignment with Islamic principles, particularly moderation and simplicity.